2006
DOI: 10.1038/nri1964
|View full text |Cite
|
Sign up to set email alerts
|

Tuning inflammation and immunity by chemokine sequestration: decoys and more

Abstract: A set of chemokine receptors are structurally unable to elicit migration or conventional signalling responses after ligand engagement. These 'silent' (non-signalling) chemokine receptors regulate inflammatory and immune reactions in different ways, including by acting as decoys and scavengers. Chemokine decoy receptors recognize distinct and complementary sets of ligands and are strategically expressed in different cellular contexts. Importantly, viruses and parasites have evolved multiple strategies to elude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
362
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 435 publications
(378 citation statements)
references
References 106 publications
8
362
0
8
Order By: Relevance
“…Cxcr7 function is important for heart development (Sierro et al, 2007), interneuron migration (Sánchez-Alcañiz et al, 2011;Wang et al, 2011), leukocyte trafficking (Cruz-Orengo et al, 2011) and for promoting breast and lung tumorigenesis (Miao et al, 2007;Luker et al, 2012). Some of these in vivo studies, as well as those conducted in vitro (Luker et al, 2010;Naumann et al, 2010), are consistent with the idea that Cxcr7 serves as a receptor that effectively scavenges Cxcl12a and does not influence downstream signaling pathways (reviewed by Mantovani et al, 2006). Despite its importance in controlling Cxcl12 activity in the tissue, the molecular mechanisms promoting the decoy function of Cxcr7 are unknown.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Cxcr7 function is important for heart development (Sierro et al, 2007), interneuron migration (Sánchez-Alcañiz et al, 2011;Wang et al, 2011), leukocyte trafficking (Cruz-Orengo et al, 2011) and for promoting breast and lung tumorigenesis (Miao et al, 2007;Luker et al, 2012). Some of these in vivo studies, as well as those conducted in vitro (Luker et al, 2010;Naumann et al, 2010), are consistent with the idea that Cxcr7 serves as a receptor that effectively scavenges Cxcl12a and does not influence downstream signaling pathways (reviewed by Mantovani et al, 2006). Despite its importance in controlling Cxcl12 activity in the tissue, the molecular mechanisms promoting the decoy function of Cxcr7 are unknown.…”
Section: Introductionsupporting
confidence: 63%
“…We monitored the subcellular localization of Cxcr7b-ECFP fusion protein relative to that of mCherry fused to Rab5, which labels early and recycling endosomes (Gorvel et al, 1991), Rab11, which is found in recycling endosomes (Ullrich et al, 1996), or Rab7, a late endosomal marker (Gorvel et al, 1991;Méresse et al, 1995), or relative to Lamp1-DsRedmonomer fusion protein, which is localized to late endosomes and lysosomes (Rohrer et al, 1996). Consistent with its suggested role as a molecular sink recycling between the membrane and intracellular compartments (Weber et al, 2004;Mantovani et al, 2006), we could identify Cxcr7b in Rab5-positive vesicles at stages when PGCs migrate (Fig. 1I).…”
Section: -Arrestins Control the Endosomal Sorting Of Cxcr7bmentioning
confidence: 94%
“…Dampening of inflammatory responses by chemokines is controlled by several mechanisms including enzyme cleavage [25] or degradation by decoy receptors [33]. The decoy receptor D6 can bind and scavenge many CC inflammatory chemokines [34,35] such as CCL2 and CCL7.…”
mentioning
confidence: 99%
“…This restores tissue homeostasis and prevents the persistent inflammation that lies at the heart of many destructive immunopathologies and promotes tumor formation (3). Resolution is aided by D6, a 7TMR related to CCR1-5, which binds 12 of the chemokine ligands for these receptors (4,5) and is expressed, at least in humans, by lymphatic endothelial cells, trophoblasts, and some leukocyte populations (6,7). D6 null mice show prolonged exaggerated responses to cutaneous inflammatory stimuli and tumor induction (8 -10), enhanced leukocyte infiltration during allergic lung inflammation (11), and increased sensitivity to experimentally induced fetal resorption (7).…”
mentioning
confidence: 99%